2011
DOI: 10.1007/s10578-011-0265-y
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Validation of the Spence Children’s Anxiety Scale

Abstract: The purpose of this study was to investigate the factorial structure and psychometric properties of the Spence Children's Anxiety Scale (SCAS) in a sample of 1,708 Spanish children aged between 8 and 12 years. The SCAS was demonstrated to have satisfactory internal consistency with the Spanish sample, and factor analysis confirmed the six-factor original model. Convergent validity was supported by correlations with the State-Trait Anxiety Inventory for Children and the welfare dimension of the Child Health and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 28 publications
4
25
0
4
Order By: Relevance
“…Scale's validity and reliability to assess anxiety, depression, and potential suicide have been shown for both community/ school (García-Olcina et al, 2014) and clinical samples (García-Olcina, Rivera-Riquelme, Cantó-Diez, Tomás-Berenguer, Bustamante, & Piqueras, 2017), with alpha values ranging between .87 and .91 (total scores) and between .67 and -.94 (for the subscales) (Garcia-Olcina et al, 2014;. Spence Children's Anxiety Scale (SCAS; Orgilés, Méndez, Spence, Huedo-Medina, & Espada, 2012). We used the specifi c phobia subscale (physical injury fears) consisting of fi ve items with 4 response alternatives (0 = never, 1 = sometimes, 2 = often, and 3 = always).…”
Section: Methodsmentioning
confidence: 99%
“…Scale's validity and reliability to assess anxiety, depression, and potential suicide have been shown for both community/ school (García-Olcina et al, 2014) and clinical samples (García-Olcina, Rivera-Riquelme, Cantó-Diez, Tomás-Berenguer, Bustamante, & Piqueras, 2017), with alpha values ranging between .87 and .91 (total scores) and between .67 and -.94 (for the subscales) (Garcia-Olcina et al, 2014;. Spence Children's Anxiety Scale (SCAS; Orgilés, Méndez, Spence, Huedo-Medina, & Espada, 2012). We used the specifi c phobia subscale (physical injury fears) consisting of fi ve items with 4 response alternatives (0 = never, 1 = sometimes, 2 = often, and 3 = always).…”
Section: Methodsmentioning
confidence: 99%
“…* p < .001. Sasagawa, et al, 2011;Li et al, 2011), robust maximum likelihood (MLR) (Nauta et al, 2004), and maximum likelihood (ML) (Orgilés et al, 2012), while borderline adequate model fit indices have also been found using least squares estimation (Muris et al, 2000) and…”
Section: Scasmentioning
confidence: 98%
“…The value of Cronbach's alpha in the adaptation of the adult form of the scale into Spanish was .89 (Orgiles, Mendez, Spence, Medina & Espada, 2012); the adaptation into Iranian was .92 (Essau, Olaya, Pasha, O'Challaga & Bray, 2012); the adaptation into German was .92 (Essau, Muris & Ederer, 2002); the adaptation into Greek was.90 (Mellon & Moutavelis, 2007); the adaptation into Japanese was .88 (Ishikawa, Oota, & Sakano, 2001) and the adaptation into South African was .92 (Muris, Schmidt, Engelbrecht, & Perold, 2002). The Guttman split-half value was reported to be .90 in the German adaptation study (Essau, Muris & Ederer, 2002).…”
Section: Spence Children's Anxiety Scale (Scas)mentioning
confidence: 99%